A polishing slurry, its preparation method, and its application in silicon carbide wafer polishing.
Patent Information
- Application Number
- CN202512054129.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2025-12-31
- Publication Date
- 2026-09-01
- Estimated Expiration
- 2045-12-31
AI Technical Summary
[0006]为了解决现有技术的不足,本发明的目的是提供一种基于双峰二氧化硅磨料的抛光液及其制备方法与在碳化硅晶圆抛光中的应用,本发明通过磨料粒径分布优化与工艺参数协同,实现高效、低损伤的超精密抛光,解决了现有8英寸及以上4H-SiC (0001)衬底CMP中“单粒径磨料难以平衡 MRR 与表面质量”“表面划痕多”“亚表面损伤深”等问题
本发明提供了一种抛光剂,通过特定比例的大粒径(80-100 nm)、小粒径(15-25nm)及中间粒径二氧化硅颗粒的协同作用,在提升8英寸及以上4H-SiC (0001)衬底CMP性能方面取得了显著的综合效益。大粒径二氧化硅(90 nm±5 nm)作为“主切削单元”,优先与衬底表面氧化层接触,提供主要机械去除力,保障高MRR。小粒径二氧化硅(20 nm±5 nm)填充大粒径磨料间的间隙,形成“弹性缓冲层”,减少大颗粒对衬底表面的直接摩擦损伤,同时对微观凸起进行精细抛光,降低表面粗糙度;双粒径体系通过优化颗粒堆积密度,抑制磨料团聚,确保大尺寸衬底抛光均匀性。与现有单粒径二氧化硅磨料及其他磨料的CMP技术相比,本发明的抛光液能够提升材料去除率,降低表面粗糙度,减少表面划痕,降低亚表面损伤(SSD),且适配工业化需求。本发明的抛光液的平均MRR较80 nm单粒径二氧化硅磨料提升20%,较20 nm 单粒径二氧化硅磨料提升175%,缩短8英寸衬底加工时间。且抛光后衬底表面粗糙度Ra低至0.054 nm±0.003 nm,实现原子级光滑表面。抛光后衬底表面累积划痕长度稳定至12.64 mm左右,较80 nm单粒径磨料累积划痕长度明显降低,与20 nm单粒径磨料累积划痕长度相近,且无明显团聚诱导划痕,提高了后续器件的可靠性。通过TEM表征,SSD深度仅1.32 nm±0.15 nm,较80 nm单粒径磨料降低15.2%,保障后续外延生长质量。本发明的抛光液能够兼容现有8英寸CMP设备,无需额外改造,抛光液组分成本低、易制备,适合大规模量产。
Smart Images

Figure CN121914632B_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of semiconductor material processing technology, and particularly relates to ultra-precision chemical mechanical polishing (CMP) technology for third-generation semiconductor silicon carbide (SiC) substrates, specifically to a polishing slurry and its preparation method and its application in silicon carbide wafer polishing. Background Technology
[0002] The information disclosed in this background section is intended only to enhance understanding of the overall background of the invention and is not necessarily to be construed as an admission or in any way implying that such information constitutes prior art known to those skilled in the art.
[0003] Chemical mechanical polishing (CMP) is a key process in semiconductor manufacturing for achieving global wafer planarization. It combines the chemical etching effect of a polishing slurry with the mechanical abrasive action of an abrasive to achieve efficient material removal and surface planarization. The polishing slurry, as the core material of the CMP process, directly determines the polishing effect. With the continuous shrinking of semiconductor device feature sizes and the widespread application of third-generation semiconductor materials such as silicon carbide (SiC), higher demands are placed on CMP technology. Especially for 8-inch and larger 4H-SiC (0001) substrates, their high hardness and high chemical inertness significantly increase the polishing difficulty. The main challenges currently facing CMP polishing slurry technology are: 1. Conventional single-peak abrasive systems struggle to balance material removal rate (MRR) and surface quality. Specifically, while large-particle abrasives (e.g., 80-100 nm) achieve high MRR, they are prone to causing scratches and deep subsurface damage (SSD) on the substrate surface. Conversely, small-particle abrasives (e.g., 15-25 nm) achieve lower surface roughness, but their MRR is often too low to meet the efficiency requirements of industrial production. Research indicates that in the CMP process on 4H-SiC substrates, the choice and concentration of the oxidant are crucial to the oxide layer formation rate, thus affecting the material removal mechanism. However, if the mechanical polishing action and chemical etching action are not matched, it is difficult to simultaneously achieve high MRR and atomically smooth surfaces.
[0004] 2. Abrasives have inherent defects that make them difficult to match with CMP technology. For example, diamond abrasives, due to their extremely high hardness (Mohs hardness 10), can achieve high MRR, but they can also cause severe surface scratches and lattice distortion, affecting subsequent epitaxial growth. Alumina abrasives have poor colloidal stability (high surface charge density makes them prone to agglomeration), requiring the addition of chemical dispersants, which may damage the integrity of the substrate surface. Although cerium dioxide abrasives have excellent polishing selectivity, large-scale synthesis with precise control of particle morphology is difficult, and they easily form stubborn Ce-OS bonds with the SiC surface, requiring complex post-cleaning processes.
[0005] Existing technologies attempt to optimize polishing slurry performance through various means, such as employing a two-step polishing process (rough polishing followed by fine polishing), adding specific oxidants, or using composite abrasives. However, these methods still have limitations: complex polishing processes prolong processing time; composite abrasives (such as a mixture of silica and alumina) may introduce chemical contaminants or lead to decreased dispersion stability; and while simply adjusting the oxidant concentration can enhance chemical reactions, insufficient mechanical removal can result in the accumulation of reaction products or the formation of corrosion pits. Furthermore, for polishing large-size substrates, the uniformity, stability, and large particle control of the polishing slurry are particularly critical, as agglomeration or sedimentation of any component can cause surface defects. Therefore, developing a polishing slurry formulation that synergistically improves material removal rate, surface quality, and reduces damage has become key to overcoming the polishing bottleneck of 8-inch and larger 4H-SiC substrates. Summary of the Invention
[0006] To address the shortcomings of existing technologies, the present invention aims to provide a polishing slurry based on bimodal silica abrasives, its preparation method, and its application in silicon carbide wafer polishing. The present invention achieves high-efficiency, low-damage ultra-precision polishing through abrasive particle size distribution optimization and process parameter synergy, solving problems such as "difficulty in balancing MRR and surface quality with single-particle-size abrasives", "numerous surface scratches", and "deep subsurface damage" in existing 8-inch and larger 4H-SiC (0001) substrate CMP.
[0007] To achieve the above objectives, the technical solution of the present invention is as follows: In a first aspect, the present invention provides a polishing fluid comprising, by mass percentage: 15% to 30% abrasive, 2% to 10% oxidant, 0.01% to 1% pH adjuster, and the remainder being water; The abrasive comprises, by percentage, 25% to 35% silica particles with a diameter of 80 to 100 nm, 55% to 65% silica particles with a diameter of 15 to 25 nm, and 1% to 10% silica particles with a diameter between the two types.
[0008] In some embodiments of the present invention, the oxidant includes any one or more of hydrogen peroxide, potassium permanganate, potassium manganate, and potassium ferrate.
[0009] In some embodiments of the present invention, the pH adjuster includes any one or more of sodium hydroxide, potassium hydroxide, sulfuric acid, nitric acid, citric acid, oxalic acid, and acetic acid.
[0010] In some embodiments of the present invention, the pH of the polishing solution is 8.0 to 10.0.
[0011] In some embodiments of the present invention, the abrasive comprises, by percentage, 25% to 35% silica particles with a particle size of 88 to 92 nm, 55% to 65% silica particles with a particle size of 18 to 22 nm, and 1% to 10% silica particles with a particle size between the two types.
[0012] In some embodiments of the present invention, the abrasive comprises, by percentage, 30% silica particles with a diameter of 90 nm, 60% silica particles with a diameter of 20 nm, and 10% silica particles with a diameter between the two types.
[0013] A second aspect of the present invention provides a method for preparing the polishing slurry described in the first aspect, comprising: Abrasives of different particle sizes are mixed, and then oxidant, pH adjuster and water are added and mixed well to obtain polishing fluid.
[0014] A third aspect of the present invention provides the application of the polishing slurry described in the first aspect in the polishing of silicon carbide wafers.
[0015] In some embodiments of the present invention, the silicon carbide wafer is a 4H-SiC substrate with a surface crystal orientation of 0001.
[0016] In some embodiments of the present invention, the 4H-SiC substrate is 8 inches or larger in size.
[0017] The beneficial effects of this invention are as follows: This invention provides a polishing agent that achieves significant comprehensive benefits in improving the CMP performance of 8-inch and larger 4H-SiC (0001) substrates through the synergistic effect of a specific ratio of large-diameter (80-100 nm), small-diameter (15-25 nm), and intermediate-diameter silica particles. Large-diameter silica (90 nm ± 5 nm) acts as the "main cutting unit," preferentially contacting the substrate surface oxide layer and providing the primary mechanical removal force, ensuring high MRR. Small-diameter silica (20 nm ± 5 nm) fills the gaps between the large-diameter abrasive particles, forming an "elastic buffer layer" that reduces direct frictional damage to the substrate surface from large particles, while simultaneously finely polishing microscopic protrusions and reducing surface roughness. The dual-diameter system optimizes particle packing density, inhibiting abrasive agglomeration and ensuring uniform polishing of large-size substrates. Compared with existing CMP technologies using single-diameter silica abrasives and other abrasives, the polishing fluid of this invention can improve material removal rate, reduce surface roughness, reduce surface scratches, reduce subsurface damage (SSD), and is suitable for industrial applications. The polishing slurry of this invention improves the average MRR by 20% compared to 80 nm single-particle-size silica abrasive and by 175% compared to 20 nm single-particle-size silica abrasive, shortening the processing time of 8-inch substrates. Furthermore, the surface roughness Ra of the polished substrate is as low as 0.054 nm ± 0.003 nm, achieving an atomically smooth surface. The cumulative scratch length on the polished substrate surface stabilizes at approximately 12.64 mm, significantly lower than that of 80 nm single-particle-size abrasive and similar to that of 20 nm single-particle-size abrasive, with no obvious agglomeration-induced scratches, improving the reliability of subsequent devices. TEM characterization shows that the SSD depth is only 1.32 nm ± 0.15 nm, a 15.2% reduction compared to 80 nm single-particle-size abrasive, ensuring the quality of subsequent epitaxial growth. The polishing slurry of this invention is compatible with existing 8-inch CMP equipment without additional modifications. The slurry components are low-cost and easy to prepare, making it suitable for large-scale mass production. Attached Figure Description
[0018] The accompanying drawings, which form part of this invention, are used to provide a further understanding of the invention. The illustrative embodiments of the invention and their descriptions are used to explain the invention and do not constitute an improper limitation of the invention.
[0019] Figure 1 This is a SEM characterization of the abrasive in the polishing slurry obtained in Example 1 of the present invention. Detailed Implementation
[0020] To address the problems existing in existing 8-inch and larger 4H-SiC (0001) substrate CMP, such as "difficulty in balancing MRR and surface quality with single-particle-size abrasives", "numerous surface scratches", and "deep subsurface damage", this invention proposes a polishing slurry, its preparation method, and its application in silicon carbide wafer polishing.
[0021] The present invention provides a polishing fluid, comprising, by mass percentage: 15%~30% abrasive, 2%~10% oxidant, 0.01%~1% pH adjuster, and the remainder being water; The abrasive comprises, by percentage, 25% to 35% silica particles with a diameter of 80 to 100 nm, 55% to 65% silica particles with a diameter of 15 to 25 nm, and 1% to 10% silica particles with a diameter between the two types.
[0022] This invention provides a polishing agent that achieves significant comprehensive benefits in improving the CMP performance of 8-inch and larger 4H-SiC (0001) substrates through the synergistic effect of a specific ratio of large-diameter (80-100 nm), small-diameter (15-25 nm), and intermediate-diameter silica particles. Large-diameter silica (90 nm ± 5 nm) acts as the "main cutting unit," preferentially contacting the substrate surface oxide layer and providing the primary mechanical removal force, ensuring high MRR. Small-diameter silica (20 nm ± 5 nm) fills the gaps between the large-diameter abrasive particles, forming an "elastic buffer layer" that reduces direct frictional damage to the substrate surface from large particles, while simultaneously finely polishing microscopic protrusions and reducing surface roughness. The dual-diameter system optimizes particle packing density, inhibiting abrasive agglomeration and ensuring uniform polishing of large-size substrates. Compared with existing CMP technologies using single-diameter silica abrasives and other abrasives, the polishing fluid of this invention can improve material removal rate, reduce surface roughness, reduce surface scratches, reduce subsurface damage (SSD), and is suitable for industrial applications. The polishing slurry of this invention improves the average MRR by 20% compared to 80 nm single-particle-size silica abrasive and by 175% compared to 20 nm single-particle-size silica abrasive, shortening the processing time of 8-inch substrates. Furthermore, the surface roughness Ra of the polished substrate is as low as 0.054 nm ± 0.003 nm, achieving an atomically smooth surface. The cumulative scratch length on the polished substrate surface stabilizes at approximately 12.64 mm, significantly lower than that of 80 nm single-particle-size abrasive and similar to that of 20 nm single-particle-size abrasive, with no obvious agglomeration-induced scratches, improving the reliability of subsequent devices. TEM characterization shows that the SSD depth is only 1.32 nm ± 0.15 nm, a 15.2% reduction compared to 80 nm single-particle-size abrasive, ensuring the quality of subsequent epitaxial growth. The polishing slurry of this invention is compatible with existing 8-inch CMP equipment without additional modifications. The slurry components are low-cost and easy to prepare, making it suitable for large-scale mass production.
[0023] It is understood that the silica particles with a particle size between the two types of silica particles are transitional particles within the particle size deviation range, that is, silica particles with a particle size between 25 nm and 80 nm.
[0024] In some embodiments of the present invention, the oxidant includes, but is not limited to, any one or more of hydrogen peroxide, potassium permanganate, potassium manganate, and potassium ferrate.
[0025] In some embodiments of the present invention, the oxidant is preferably hydrogen peroxide, which mainly plays the role of promoting the formation of a surface oxide layer.
[0026] Hydrogen peroxide lays the foundation for efficient chemical mechanical polishing, promoting the formation of a soft oxide layer and precisely controlling the oxidation process. Hydrogen peroxide works synergistically with abrasives and the pH environment. Large-particle abrasives (80–100 nm) are primarily responsible for efficiently scraping away the oxide layer softened by hydrogen peroxide, playing a key role in improving material removal rates. Small-particle abrasives (15–25 nm) effectively repair microscopic scratches that may be left by large-particle abrasives, playing a role in fine grinding and finishing. Hydrogen peroxide, by promoting a uniform soft layer, provides an ideal prerequisite for this combined coarse and fine mechanical action, allowing the advantages of the dual-particle abrasive system to be fully realized. The pH value of the polishing slurry has a significant impact on the stability and oxidizing efficacy of hydrogen peroxide.
[0027] In some embodiments of the present invention, the pH adjuster includes, but is not limited to, any one or more of sodium hydroxide, potassium hydroxide, sulfuric acid, nitric acid, citric acid, oxalic acid, and acetic acid.
[0028] In some embodiments of the present invention, the pH adjuster is preferably sodium hydroxide, which mainly serves to adjust the pH of the polishing solution.
[0029] In some embodiments of the present invention, the polishing solution has a pH of 8.0 to 10.0.
[0030] It is important to note that a slightly alkaline pH range of 8-10 is crucial for achieving the synergistic effect of the components. Within this pH range, the absolute value of the zeta potential on the abrasive surface is relatively high, and the particles maintain good dispersion due to electrostatic pressure, effectively preventing agglomeration and the formation of destructive large particles. This environment ensures that the hydrogen peroxide oxidation reaction is mild and controllable, effectively generating a softening layer while avoiding the formation of corrosion pits or uneven oxidation on the surface due to excessively rapid or vigorous reactions. The corrosiveness of slightly alkaline conditions to CMP equipment is far lower than that of strongly acidic conditions, making this polishing fluid highly compatible with existing 8-inch CMP equipment and meeting the requirements of industrial production for process compatibility and equipment friendliness.
[0031] In this invention, the components work synergistically in a weakly alkaline environment (pH 8-10). In this environment, hydrogen peroxide continuously and stably oxidizes the surface of the 4H-SiC substrate to form a softer silica or silicate layer. This soft film is then efficiently and mechanically removed by silica abrasives of varying particle sizes. This efficient and stable oxidation-removal cycle provides a foundation for achieving high material removal rates and low surface damage. Furthermore, under weakly alkaline conditions, the silica abrasive surface carries a negative charge, enhancing electrostatic repulsion between particles and improving dispersion stability, which is beneficial for particle size synergy. Large-particle abrasives (80-100 nm) act as the "main force," scraping away most of the chemically softened oxide layer and directly contributing to the high material removal rate. Small-particle abrasives (15-25 nm) act as "fine-tuning craftsmen," filling the gaps between large particles for finer grinding, effectively repairing microscopic defects, and thus significantly reducing surface roughness and scratches. Furthermore, the combination of large and small particle sizes optimizes the pressure distribution during the polishing process, avoiding excessive stress concentration, which helps reduce surface scratches and lower the subsurface damage (SSD) depth. Transitional particles play a good transition and filling role, making the particle size distribution of the abrasive system more continuous and the synergistic effect better.
[0032] In some embodiments of the present invention, the abrasive comprises, by percentage, 25% to 35% silica particles with a particle size of 88 to 92 nm, 55% to 65% silica particles with a particle size of 18 to 22 nm, and 1% to 10% silica particles with a particle size between the two types.
[0033] In some embodiments of the invention, the abrasive comprises, by percentage, 30% silica particles with a diameter of 90 nm, 60% silica particles with a diameter of 20 nm, and 10% silica particles with a diameter between the two types.
[0034] In some embodiments of the present invention, the mass percentage of abrasive in the polishing fluid may specifically be 15%, 16%, 17%, 18%, 19%, 20%, 21%, 22%, 23%, 24%, 25%, 26%, 27%, 28%, 29%, 30%, etc. The mass percentage of abrasive is preferably 18% to 25%, more preferably 18% to 22%, and most preferably 20%.
[0035] In some embodiments of the present invention, the mass percentage of the oxidant in the polishing slurry may specifically be 2%, 3%, 4%, 5%, 6%, 7%, 8%, 9%, 10%, etc. The mass percentage of the abrasive is preferably 3% to 8%, more preferably 4% to 6%, and most preferably 5%.
[0036] In some embodiments of the present invention, the mass percentage of the pH adjuster in the polishing fluid may specifically be 0.01%, 0.02%, 0.03%, 0.04%, 0.05%, 0.06%, 0.07%, 0.08%, 0.09%, 0.1%, 0.2%, 0.3%, 0.4%, 0.5%, 0.6%, 0.7%, 0.8%, 0.9%, 1%, etc. The mass percentage of the abrasive is preferably 0.3% to 0.8%, more preferably 0.4% to 0.6%, and most preferably 0.5%.
[0037] In some embodiments of the present invention, the polishing fluid, by mass percentage, comprises: 18% to 25% abrasive, 3% to 8% oxidant, 0.3% to 0.8% pH adjuster, and the remainder being water; The abrasive comprises, by percentage, 25% to 35% silica particles with a diameter of 80 to 100 nm, 55% to 65% silica particles with a diameter of 15 to 25 nm, and 1% to 10% silica particles with a diameter between the two types.
[0038] In some embodiments of the present invention, the polishing fluid, by mass percentage, comprises: 20% abrasive, 5% oxidant, 0.5% pH adjuster, and the remainder being water; The abrasive comprises, by percentage, 30% silica particles with a diameter of 90 nm, 60% silica particles with a diameter of 20 nm, and 10% silica particles with a diameter between the two types.
[0039] The present invention also provides a method for preparing the polishing slurry, comprising: Abrasives of different particle sizes are mixed, and then oxidant, pH adjuster and water are added and mixed well to obtain polishing fluid.
[0040] In the preparation process of this invention, large-particle-size silica and small-particle-size silica are mixed in a ratio of approximately 1:2. Then, oxidant, pH adjuster and water are added to the abrasive in proportion and mixed evenly to obtain a polishing liquid.
[0041] The present invention also provides an application of the polishing slurry in the polishing of silicon carbide wafers.
[0042] In some embodiments of the present invention, the application involves using a polishing slurry to perform chemical mechanical polishing on a silicon carbide wafer, after which it can be directly cleaned using a silicon carbide wafer cleaning device.
[0043] In some embodiments of the present invention, the silicon carbide wafer is a 4H-SiC substrate with a surface crystal orientation of 0001.
[0044] In some embodiments of the present invention, the size of the 4H-SiC substrate is preferably 8 inches or more.
[0045] To enable those skilled in the art to better understand the technical solution of the present invention, the technical solution of the present invention will be described in detail below with reference to specific embodiments.
[0046] Example 1 This embodiment provides a polishing slurry based on bimodal SiO2 abrasive, the raw material composition of which is as follows: Bimodal SiO2 abrasive: 30% large-diameter (90 nm ± 5 nm) SiO2 particles, 60% small-diameter (20 nm ± 5 nm) SiO2 particles, and the remaining 10% transitional particles within the particle size range. The mass fraction of the bimodal silica abrasive is 20 wt%.
[0047] Oxidizing agent: Hydrogen peroxide 5 wt%.
[0048] pH adjuster: Sodium hydroxide 0.5 wt%.
[0049] Add deionized water to bring the total to 100 wt%.
[0050] The pH is 9.
[0051] The preparation method of the polishing agent includes the following steps: Large-diameter SiO2 particles, small-diameter SiO2 particles, and transition-state particles are mixed evenly according to their respective proportions to obtain abrasive.
[0052] Add oxidant, pH adjuster and deionized water to the abrasive in proportion, and mix well to obtain polishing fluid.
[0053] The polishing slurry prepared in this embodiment was used for chemical mechanical polishing of an 8-inch N-type 4H-SiC (0001) substrate. After polishing, the substrate was cleaned using a silicon carbide wafer cleaning system.
[0054] The following checks are performed during polishing: MRR test: The substrate mass loss was calculated every 3 hours (12 hours in total) using the weighing method, and the MRR was converted to 160 nm / h.
[0055] Surface roughness (Ra) test: Five random points in a 5 μm × 5 μm area were tested on the polished 8-inch N-type 4H-SiC (0001) substrate using atomic force microscopy, with an average Ra = 0.054 ± 0.003 nm.
[0056] Surface scratch test: The polished 8-inch N-type 4H-SiC (0001) substrate was tested using a SiC defect detection device, and the cumulative scratch length was found to be 12.64 mm.
[0057] SSD testing: The cross-sectional sample was prepared using a focused ion beam and combined with a high-resolution transmission electron microscope to measure the SSD depth as 1.32 nm ± 0.15 nm.
[0058] Example 2 This embodiment provides a polishing slurry based on bimodal SiO2 abrasive, which differs from Example 1 in that: the bimodal SiO2 abrasive consists of large-particle (90 nm ± 5 nm) SiO2 particles (25% of the total), small-particle (20 nm ± 5 nm) SiO2 particles (65% of the total), and the remaining 10% is transitional particles within the particle size deviation range. The mass fraction of the bimodal silica abrasive is 20 wt%. The remaining raw material composition, preparation method, and polishing method are completely consistent with those of Example 1.
[0059] The performance test was conducted using the method described in Example 1.
[0060] MRR=145 nm / h, Ra=0.052±0.003 nm, cumulative surface scratch length=11.13 mm, SSD depth=1.22 nm±0.15 nm.
[0061] After polishing with the polishing slurry provided in this embodiment, the 8-inch N-type 4H-SiC (0001) substrate exhibits superior surface quality and a slightly lower material removal rate. Due to the increased proportion of small-diameter SiO2 particles, the fine grinding and filling repair effects are enhanced, further reducing surface roughness (Ra) and cumulative scratch length, resulting in shallower subsurface damage depth. However, the reduced proportion of large-diameter SiO2 particles correspondingly weakens the dominant mechanical removal capability, thus the material removal rate (MRR) is slightly lower than in Example 1.
[0062] Example 3 This embodiment provides a polishing slurry based on bimodal SiO2 abrasive, which differs from Example 1 in that: the bimodal SiO2 abrasive consists of large-particle (90 nm ± 5 nm) SiO2 particles (35% of the total), small-particle (20 nm ± 5 nm) SiO2 particles (55% of the total), and the remaining 10% is transitional particles within the particle size deviation range. The mass fraction of the bimodal silica abrasive is 20 wt%. The remaining raw material composition, preparation method, and polishing method are completely consistent with those of Example 1.
[0063] Performance testing was conducted using the method described in Example 1: MRR=185 nm / h, Ra=0.057±0.003 nm, cumulative surface scratch length=15.75 mm, SSD depth=1.43 nm±0.18 nm.
[0064] After polishing with the polishing slurry provided in this embodiment, the 8-inch N-type 4H-SiC (0001) substrate exhibits a higher material removal rate, with a slight sacrifice in surface quality. Due to the increased proportion of large-diameter SiO2 particles, the mechanical abrasive capability is enhanced, further improving the material removal rate (MRR). However, the repair and finishing effects of small-diameter SiO2 particles are relatively weakened, increasing the risk of microscopic scratches on the surface. The surface roughness (Ra) and scratch length are slightly higher than in Example 1, but still significantly better than traditional polishing slurries using a single 80 nm large-diameter abrasive.
[0065] Example 4 This embodiment provides a polishing slurry based on bimodal SiO2 abrasive, which differs from Example 1 in that: oxidant: hydrogen peroxide 2 wt%. The remaining raw material composition, preparation method, and polishing method are completely consistent with those of Example 1.
[0066] Performance testing was conducted using the method described in Example 1: MRR=105 nm / h, Ra=0.058±0.003 nm, cumulative surface scratch length=13.86 mm, SSD depth=1.31 nm±0.16 nm.
[0067] After polishing with the polishing slurry provided in this embodiment, the removal rate of the 8-inch N-type 4H-SiC (0001) substrate was relatively low: this concentration is at the critical point of effective oxidation, and the MRR will be lower than that of Example 1 (5%). The weaker chemical action resulted in a slower rate or insufficient thickness of the softened oxide layer formed on the substrate surface, limiting the mechanical removal efficiency of the abrasive. The surface quality was good, but lower than that of Example 1. The lower chemical etching power helps reduce the risk of over-polishing and pitting. The oxide layer was too thin, leading to discontinuous or uneven mechanical removal, which in turn slightly increased or fluctuated the surface roughness (Ra).
[0068] Example 5 This embodiment provides a polishing slurry based on bimodal SiO2 abrasive, which differs from Example 1 in that: oxidant: hydrogen peroxide 10 wt%. The remaining raw material composition, preparation method, and polishing method are completely consistent with those of Example 1.
[0069] Performance testing was conducted using the method described in Example 1: MRR=179 nm / h, Ra=0.066±0.004 nm, cumulative surface scratch length=23.20 mm, SSD depth=1.57 nm±0.18 nm.
[0070] After polishing with the polishing slurry provided in this embodiment, the removal rate of the 8-inch N-type 4H-SiC (0001) substrate is further improved. Strong oxidation is expected to accelerate the formation of the softening layer, and the MRR is slightly higher than that in Example 1. The surface quality of the substrate decreases, and excessive chemical corrosion leads to uneven oxide layer texture or local over-corrosion (forming corrosion pits), which deteriorates the surface roughness and increases the scratch length.
[0071] Comparative Example 1 This comparative example provides a polishing slurry based on single-peak SiO2 and is used for polishing an 8-inch 4H-SiC substrate.
[0072] The raw material composition of the polishing slurry based on unimodal SiO2 in this comparative example is as follows: Single-peak SiO2 abrasive: SiO2 particles with a diameter of 80 nm ± 5 nm, with a mass fraction of 20 wt% in the polishing slurry (consistent with the total abrasive concentration in Example 1). The remaining raw materials are completely consistent with those in Example 1.
[0073] The polishing slurry is prepared as follows: A polishing solution is obtained by uniformly mixing single-peak SiO2 particles, hydrogen peroxide, sodium hydroxide, and deionized water.
[0074] The polishing slurry prepared in this comparative example was used for chemical mechanical polishing of an 8-inch N-type 4H-SiC (0001) substrate. After polishing, the substrate was cleaned using a silicon carbide wafer cleaning system.
[0075] Performance testing was conducted using the method described in Example 1: MRR=133 nm / h, Ra=0.057 nm±0.003 nm, cumulative surface scratch length=44.72 mm, SSD depth=1.52 nm±0.18 nm.
[0076] Comparative Example 2 This comparative example provides a polishing slurry based on single-peak SiO2 and is used for polishing an 8-inch 4H-SiC substrate.
[0077] The raw material composition of the polishing slurry based on unimodal SiO2 in this comparative example is as follows: Single-peak SiO2 abrasive: SiO2 particles with a particle size of 20 nm ± 5 nm, with a mass fraction of 20 wt% in the polishing slurry (consistent with the total abrasive concentration in Example 1). The remaining raw materials are completely consistent with those in Example 1.
[0078] The polishing slurry is prepared as follows: A polishing solution is obtained by uniformly mixing single-peak SiO2 particles, hydrogen peroxide, sodium hydroxide, and deionized water.
[0079] The polishing slurry prepared in this comparative example was used for chemical mechanical polishing of an 8-inch N-type 4H-SiC (0001) substrate. After polishing, the substrate was cleaned using a silicon carbide wafer cleaning system.
[0080] Performance testing was conducted using the method described in Example 1: MRR=58 nm / h, Ra=0.052 nm±0.003 nm, cumulative surface scratch length=11.36 mm, SSD depth=1.24 nm±0.18 nm.
[0081] Comparative Example 3 This comparative example provides a polishing slurry based on bimodal SiO2 abrasive. The difference between this slurry and Example 1 is that the amount of pH adjuster (sodium hydroxide) is adjusted to achieve a pH of 7. The remaining raw material composition, preparation method, and polishing method are completely consistent with those of Example 1.
[0082] Performance testing was conducted using the method described in Example 1: MRR=93 nm / h, Ra=0.065±0.004 nm, cumulative surface scratch length=28.59 mm, SSD depth=1.63±0.18 nm.
[0083] In a neutral environment with pH=7, due to poor dispersion stability and imbalance of chemical-mechanical interaction, the performance of the polishing slurry is significantly worse than that of Example 1 of the present invention (pH=9), with a significant decrease in material removal rate (MRR), an increase in surface scratches, and poor roughness.
[0084] Comparative Example 4 This comparative example provides a polishing slurry based on bimodal SiO2 abrasive. The difference between this slurry and Example 1 is that the amount of pH adjuster (sodium hydroxide) is adjusted to make the pH of the polishing slurry 11. The remaining raw material composition, preparation method, and polishing method are completely consistent with those of Example 1.
[0085] Performance testing was conducted using the method described in Example 1: MRR=199 nm / h, Ra=0.073 nm, cumulative surface scratch length=38.96 mm, SSD depth=1.84±0.20 nm.
[0086] When the pH value increases to 11, the material removal rate (MRR) increases significantly due to excessive corrosion, but surface scratches increase and the surface roughness is poor.
[0087] Results Analysis The bimodal SiO2 abrasive system in Example 1, through the synergistic effect of large-particle "main cutting" and small-particle "gap filling and buffering," significantly improves surface quality and reduces damage while enhancing the MRR. The single-particle SiO2 (80 nm) system in Comparative Example 1, due to its large particle packing gaps and concentrated local pressure, exhibits a lower MRR and larger scratches and SSD. The single-particle SiO2 (20 nm) system in Comparative Example 2 demonstrates the best performance in terms of surface quality (roughness, scratches, and subsurface damage), confirming the inherent advantages of small-particle abrasives in achieving ultra-smooth, low-damage surfaces. However, its material removal rate (58 nm / h) is extremely low, less than half that of Example 1 (160 nm / h), making its processing efficiency unacceptable and a fatal weakness for industrial applications.
[0088] Example 1 successfully combines the advantages of Comparative Example 1 and Comparative Example 2 while avoiding their disadvantages: using large particles (90 nm) ensures a high material removal rate, while using small particles (20 nm) for filling and buffering results in excellent surface quality close to that of a pure small particle system. Through the synergistic effect of the bimodal system, a perfect balance between efficiency and quality is achieved.
[0089] The above description is merely a preferred embodiment of the present invention and is not intended to limit the invention. Various modifications and variations can be made to the present invention by those skilled in the art. Any modifications, equivalent substitutions, improvements, etc., made within the spirit and principles of the present invention should be included within the scope of protection of the present invention.
Claims
1. A polishing liquid, characterized in that, By mass percentage, it includes: 15%~30% abrasive, 2%~10% oxidant, 0.01%~1% pH adjuster, and the remainder is water; In terms of quantity percentage, the abrasive contains 25% to 35% silica particles with a particle size of 80 to 100 nm, 55% to 65% silica particles with a particle size of 15 to 25 nm, and 1% to 10% silica particles with a particle size between the two types. The polishing solution has a pH of 8.0~10.0; The oxidant includes any one or more of hydrogen peroxide, potassium permanganate, potassium manganate, and potassium ferrate. The pH adjuster includes any one or more of sodium hydroxide, potassium hydroxide, sulfuric acid, nitric acid, citric acid, oxalic acid, and acetic acid.
2. The polishing slurry as described in claim 1, characterized in that, The abrasive comprises, by percentage, 25% to 35% silica particles with a diameter of 88 to 92 nm, 55% to 65% silica particles with a diameter of 18 to 22 nm, and 1% to 10% silica particles with a diameter between the two types.
3. The polishing slurry as described in claim 1, characterized in that, The abrasive comprises, by percentage, 30% silica particles with a diameter of 90 nm, 60% silica particles with a diameter of 20 nm, and 10% silica particles with a diameter between the two types.
4. A method for preparing the polishing slurry according to any one of claims 1-3, characterized in that, include: Abrasives of different particle sizes are mixed, and then oxidant, pH adjuster and water are added and mixed well to obtain polishing fluid.
5. The application of the polishing slurry according to any one of claims 1-3 in the polishing of silicon carbide wafers.
6. The application as described in claim 5, characterized in that, The silicon carbide wafer is a 4H-SiC substrate with a surface crystal orientation of 0001.
7. The application as described in claim 6, characterized in that, The 4H-SiC substrate has a size of 8 inches or larger.
Citation Information
Patent Citations
Silicon carbide polishing solution containing composite silica sol abrasive as well as preparation method and application of silicon carbide polishing solution
CN119799165A